Learning Tools Based on Outcome Based Education to Improve Student Learning Outcomes - Handayani, Ni Nyoman Lisna; Wiguna, Komang Wahyu (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
Currently, high quality and competent human resources are needed in the world of work. To achieve this, activities must be achieved as early as possible, which can be started from college by applying the Outcome Based Education (OBE) learning method. This research aims to develop learning tools for scientific courses in the form of valid, practical and effective outcome based education semester learning plans to improve student learning outcomes. The learning device development model used in this research is define, design, and develop, by modifying the 4-D model (Four D model). Learning device validity data was collected by a validation questionnaire. Practicality data was collected through questionnaires on the responses of lecturers and students to learning tools, and questionnaires on the implementation of learning tools. Data analysis was carried out descriptively. Based on the research results obtained: (1) the validity of learning devices is in the valid category with a validity value of RPS 3.52, (2) the practicality of learning devices is in the very practical category with value of 3.43, the average lecturer response is 3.71 and student response is 3.54, (3) the effectiveness of learning tools is in the effective category, with an average learning achievement test score of 79.54 and completeness of 88.24%. Based on the findings of the research results, it was concluded that learning tools met the criteria of being valid, practical, and effective in improving student learning outcomes tests, so that they could be implemented in a wider scope.